Aprendizagem significativa como alicerce para metodologias ativas no ensino de ciências: uma interlocução em prol da educação de jovens e adultos - AUGUSTINHO, Elizabeth (Universidade Federal do Pará, 2021)
The article presents reflections on how the education of young people and adults can be reframed, in the search for an active participation of the student, in which he is the protagonist and subject of his learning. It highlights the importance of teacher training to work in this type of teaching. This is a bibliographic, descriptive research, based on the experience in the classroom and through the reading of vast bibliographic material, which motivated the deepening of the theme, prioritizing reference authors, such as: Freire, Ausubel, Moran, Chassot. In addition to presenting fundamental concepts related to meaningful learning, the importance of active methodologies is highlighted, which can become effective strategies for meaningful learning in science in youth and adult education.